2015
DOI: 10.1227/neu.0000000000000746
|View full text |Cite
|
Sign up to set email alerts
|

Outpatient Cervical and Lumbar Spine Surgery is Feasible and Safe

Abstract: This series of 1449 consecutive outpatient microsurgical spine decompressions adds to the growing literature in favor of outpatient spinal surgery in properly selected patients. In our study, 99.8% of the patients were successfully discharged either to their homes or to a hotel on the day of surgery. The overall complication rate was 3.5%, surgical mortality was 0%, and only 1.5% had to be admitted to a hospital within 3 months after surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
42
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 87 publications
(44 citation statements)
references
References 49 publications
2
42
0
Order By: Relevance
“…The majority of studies used the more common Tsukayama et al [172] classification system, in which acute (early) infections occur within one month of the index procedure and chronic (late) infections occur more than one month after the index procedure. The pooled average early SSI rate among 14,517 patients was 2.1% (median, 2.6%; range, 0.5%–16.7%) [11,13,20,22,25,32,78,82–84,86,142,147,156,164,167,170,171] compared with 0.8% (median, 0.9%; range, 0.1%–4.7%) for pooled average late SSI rate among 12,238 patients [11,13,54,83,167,171]. In terms of specific types of spine operations, 52 studies evaluated SSI rates among patients who underwent spinal fusion [9,10,14,15,21,24,27,30,33,42,43,46,52,56,58,62,63,68–70,72,75,76,92,103,105,107–109,111,113–115,119,120,123,125,128,133,139,141–144,146,150,151,157,161,162,164,173].…”
Section: Resultsmentioning
confidence: 99%
“…The majority of studies used the more common Tsukayama et al [172] classification system, in which acute (early) infections occur within one month of the index procedure and chronic (late) infections occur more than one month after the index procedure. The pooled average early SSI rate among 14,517 patients was 2.1% (median, 2.6%; range, 0.5%–16.7%) [11,13,20,22,25,32,78,82–84,86,142,147,156,164,167,170,171] compared with 0.8% (median, 0.9%; range, 0.1%–4.7%) for pooled average late SSI rate among 12,238 patients [11,13,54,83,167,171]. In terms of specific types of spine operations, 52 studies evaluated SSI rates among patients who underwent spinal fusion [9,10,14,15,21,24,27,30,33,42,43,46,52,56,58,62,63,68–70,72,75,76,92,103,105,107–109,111,113–115,119,120,123,125,128,133,139,141–144,146,150,151,157,161,162,164,173].…”
Section: Resultsmentioning
confidence: 99%
“…8,10,22,25,33,47 Helseth et al reported on a series of 1073 consecutive patients undergoing lumbar procedures at a freestanding neurosurgical clinic with a successful discharge rate of 99.8% on the day of surgery. 19 No patients died within 30 days, and the 90-day readmission rate was 1.5%. Nine patients (0.6%) suffered a postoperative hematoma, which was recognized and evacuated postoperatively, and these patients were subsequently discharged the same day.…”
Section: Outcomes Lumbar Laminectomy and Discectomymentioning
confidence: 91%
“…In the current health care climate, surgical practices have shifted toward performing procedures in outpatient facilities in order to maximize efficiency and minimize costs. [19][20][21][22][23][24][25][26][27][28][29] Prior literature has reported the safety and efficacy of ACDF procedures in the outpatient and inpatient settings. 7,[9][10][11][12][13][14][15] Among other concerns, narcotic usage is associated with a significant side-effect profile, including nausea, vomiting, constipation, drowsiness, coughing, difficulty with deep breathing, transient impairment of psychomotor skills, and impaired bowel and bladder function.…”
Section: Discussionmentioning
confidence: 99%